2016
DOI: 10.1007/s00261-016-0638-6
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid FDG-PET/MR compared to FDG-PET/CT in adult lymphoma patients

Abstract: FDG-PET/MR offers an equivalent whole-body staging examination as compared with PET/CT with an improved radiation safety profile in lymphoma patients. Correlation of ADC to SUVmax was weak, understating their lack of equivalence, but not undermining their potential synergy and differing importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…In fact, the PET-MR reconstruction software, approved for clinical use worldwide, automatically corrects for the delay between the time of FDG injection and the time of PET data acquisition for each bed position. Moreover, several studies have demonstrated comparable SUV values between PET-CT and subsequently acquired PET-MR (Pace et al , 2014; Atkinson et al , 2016; Pujara et al , 2016). …”
Section: Discussionmentioning
confidence: 93%
“…In fact, the PET-MR reconstruction software, approved for clinical use worldwide, automatically corrects for the delay between the time of FDG injection and the time of PET data acquisition for each bed position. Moreover, several studies have demonstrated comparable SUV values between PET-CT and subsequently acquired PET-MR (Pace et al , 2014; Atkinson et al , 2016; Pujara et al , 2016). …”
Section: Discussionmentioning
confidence: 93%
“…The PET/MR reconstruction software automatically corrects for incubation time for each bed position. Moreover, several studies have demonstrated comparable performance between PET/CT and subsequently acquired PET/MR as quantified by SUV measurements (22,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…101,102 It follows that the combination of whole body MRI with DWI and FDG PET would offer the advantages of both technologies while minimizing radiation dose to these patients, many of whom require serial follow-up examinations over a long period of time. To this end, several studies have compared PET/MRI with PET/CT in the evaluation of lymphoma, showing high concordance between staging and comparable SUVmax measurements using both modalities in adult [103][104][105] and pediatric patients. 106,107…”
Section: Pelvicmentioning
confidence: 99%